GARDENING AND WINE-GROWING IN THE LATE MEDIEVAL DAGESTAN - Aliev, B G (History, Archeology and Ethnography of the Caucasus, 2015)
Basing on the analysis and generalization of the available materials the author of the article studies the problem of fruit and wine growing in late feudal Dagestan. It is noted that fruit and wine growing developed in flat, Southern and submontane Dagestan. The author emphasizes the development of fruit and wine growing in the river valleys of mountainous Dagestan (Koisubulu, Tekhnutsal, Gidatl, Tsudakhar, Salataviya), and the fact that for many communities here fruit and wine growing became the main branch of occupation that brought primary income for existence.
Keywords: fruit growing; wine growing; Derbent and Derbent domain; Southern Dagestan; Tabasaran; Kaitag; Kumyk domein; mountainous Dagestan; Khindalal; Tsudakhar; Salataviya; Gidatl